Education Through Audiovisual Media To Increase Students' Knowledge And Attitudes About Oral Health - Qosim, Nanang; Sukendro, Sulur Joyo; Salikun, Salikun; Sadimin, Sadimin (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
This research examines dental and oral health problems in Islamic boarding schools, which are influenced by the lack of knowledge and attitudes of the students. Knowledge of dental and oral health is an effort that is included in prevention to maintain healthy teeth and mouth, if dental and oral health is not paid attention to it can cause problems with dental and oral disease. This research aims to increase students' knowledge and attitudes towards dental and oral health through audio-visual education at the Putra Al-Badriyah Mranggen Islamic boarding schools. This type of research is a quasi-experimental pre-post test with control group design with a sample of 50 students, using a questionnaire given before and after the counseling intervention through audio-visual education, with data analysis using the Wilcoxon test. The results showed a significant increase in students' knowledge and attitudes (p: 0.000 α (0,05) and yaitu p: 0,000 α (0,05). In conclusion, audio visual education is effective in increasing students' knowledge and attitudes about dental and oral health.